2014
DOI: 10.1371/journal.pone.0094018
|View full text |Cite
|
Sign up to set email alerts
|

Delay in cART Initiation Results in Persistent Immune Dysregulation and Poor Recovery of T-Cell Phenotype Despite a Decade of Successful HIV Suppression

Abstract: BackgroundSuccessful combination antiretroviral therapy (cART) increases levels of CD4+ T-cells, however this increase may not accurately reflect long-term immune recovery since T-cell dysregulation and loss of T-cell homeostasis often persist. We therefore assessed the impact of a decade of effective cART on immune regulation, T-cell homeostasis, and overall T-cell phenotype.MethodsWe conducted a retrospective study of 288 HIV+ cART-naïve patients initiating therapy. We identified 86 individuals who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
6
14
1
Order By: Relevance
“…count and current CD4:CD8 ratio, which has not been reported in previous smaller studies in children [5]. While different study designs and different definitions of a 'normal' CD4:CD8 ratio make direct comparisons difficult, in two adult studies in which the length of time on ART was comparable to that in this study, there were still considerably lower rates of ratio normalization (37% and 16%, respectively) [13,14]. However, nadir CD4 counts were lower in both adult cohorts (medians 130 cells/lL and 157 and 136 cells/lL for the CD4:CD8 ≥ 0.9 and < 0.9 groups, respectively) compared with this cohort (median 425 cells/lL).…”
Section: Discussioncontrasting
confidence: 69%
“…count and current CD4:CD8 ratio, which has not been reported in previous smaller studies in children [5]. While different study designs and different definitions of a 'normal' CD4:CD8 ratio make direct comparisons difficult, in two adult studies in which the length of time on ART was comparable to that in this study, there were still considerably lower rates of ratio normalization (37% and 16%, respectively) [13,14]. However, nadir CD4 counts were lower in both adult cohorts (medians 130 cells/lL and 157 and 136 cells/lL for the CD4:CD8 ≥ 0.9 and < 0.9 groups, respectively) compared with this cohort (median 425 cells/lL).…”
Section: Discussioncontrasting
confidence: 69%
“…In conclusion, the importance of timely initiation of cART before profound immunodeficiency occurs in children should not be underestimated, as has been reported previously [9], [11], [12], [13], [14]. The Ministry of Health in Rwanda has recognized this and has adjusted its guidelines accordingly.…”
Section: Discussionmentioning
confidence: 74%
“…Ndumbi et al monitored the longitudinal changes in CD4:CD8 ratio over a 10-year follow-up in ART treated patients [23]. They demonstrated that in patients with a CD4 T cell count B 200 cells/mm 3 , the CD4:CD8 ratio failed to normalize.…”
Section: Resultsmentioning
confidence: 99%